Dual-matrix interface strength of 3D printed continuous carbon fiber reinforced composites: Quantitative assessment methodology and critical influencing factors - Xiaofei Lou; Lei Dong; Xin'an Tang; Xiaohui Nan; Teng Zhang; Li Zhao (Additive Manufacturing Letters)
In 3D printed continuous carbon fiber reinforced dual-matrix composites, the resin matrix in the carbon fiber prepreg filament is not the same with the matrix in the composite, and the dual-matrix interface plays an important role on the mechanical properties of structures. In this paper, a method for testing the interface shear strength (IFSS) of the dual-matrix is proposed. The interfaces between carbon fiber reinforced polyamide-6 prepreg filament and different polylactic acid matrices are selected, and the strengths of the dual-matrix interface are investigated under different printing temperatures, printing speeds, layer thicknesses, and prepreg filament volume fractions. The results show that the polylactic acid matrix with lower crystallinity is capable to form stronger interface with the polyamide-6 material. The printing temperature and printing speed need to be controlled within a certain range to ensure a reasonable viscosity range and printing quality, which will achieve a higher dual-matrix IFSS. The increase of prepreg filament volume fraction and the decrease of layer thickness are conducive to the improvement of dual-matrix interfacial properties. In addition, finite element analysis based on the cohesive model is used to analyze the interface debonding behavior, which validates the test method proposed in this paper.